Investigating the Application of 3D Printing Techniques in the Medical Industry - Morar, Bhaven (2017)
3D Printing or Additive Manufacturing (AM) is seen as a group of technologies that have the ability to fabricate components through successive layers. This dissertation provides an understanding of how this productive technology is implemented in the medical industry. It uses a mixed methods research approach, extracting both qualitative and quantitative data from three organisations in the medical industry. The medical applications under investigation comprise of prosthetic hands, hip implants and hearing aids.